Antioxidant activity of Eucheuma cottonii Seaweed Extracts from Central Mawasangka Waters - Megawati, Megawati; Samaria, Siti; Baari, Muhammad Jalil (Jurnal Pijar Mipa, 2024)
Eucheuma cottonii is one type of seaweed that has the potential to be an antioxidant. This seaweed grows and is distributed in various waters of Indonesia, especially in Southeast Sulawesi. However, information regarding the antioxidant activity and the compound content of E. cottonii in this area is still limited. Therefore, this research aims to determine the compound and antioxidant activity profile in E. cottonii. The study used laboratory experimental methods. The research stages were preparation (seaweed sampling), extraction, qualitative phytochemical screening, and antioxidant assay. The initial identification of compounds using qualitative phytochemical screening methods with three extraction solvents: ethanol, ethyl acetate, and n-hexane. Meanwhile, the antioxidant test employed the DPPH (2,2-diphenyl-1-picrylhydrazyl) method. The results of qualitative phytochemical screening revealed that the seaweed extract of E. cottonii contains saponins, tannins, and terpenoids. The antioxidant assay using the DPPH method indicated that among the three extraction solvents used, ethanol extract exhibited a very strong antioxidant activity (with an IC50 of 30,036 ppm), compared to ethyl acetate extract (IC50 of 182,179 ppm) and n-hexane extract (IC50 of 641,454 ppm). This study concluded that E. cottonii seaweed has the potential to be developed as a source of natural antioxidants or raw material for the discovery of antioxidant medicines in the future.